Penggunaan Aplikasi Wordwall Pada Pembelajaran Sejarah Di SMA Negeri 5 Pontianak - Baiyeni Amalia Hasanah; Andang Firmansyah; Haris Firmansyah (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Palangka Raya, 2023)
With the impacts of rapid technological advances, it is undeniable that many various technology-based learning media are created. Learning media has many benefits, one of which is as a tool to convey learning objectives. Moreover, for history learning, it is no stranger that many students are not interested in learning history. Because history learning contains various kinds of events that require students to remember all these things. Therefore, the use of media is needed in history learning. The purpose of the research was to description the use of Wordwall app in history learning in XI class of SMAN 5 Pontianak. The research method uses descriptive qualitative. The research location at SMAN 5 Pontianak. The data collection technique uses interviews, observations, and documentation. The source of research informants is history teachers and class XI students of SMAN 5 Pontianak. The research results are that the use of Wordwall app can help teachers convey historical materials that are difficult for students to understand. Meanwhile, for students, learning history using Wordwall app is a new and fun experience, so students more interested and active during the history learning process.